Intellectual crimes and serious violation of human rights in Turkey: a narrative inquiry - Aydin, Hasan; Avincan, Koksal (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2020)
After the crackdown following the failed coup attempt of 15 July 2016, the Turkish government persecuted hundreds of thousands of people, and much damage has continued to afflict Turkish civil, legal and political life. Many intellectuals have been arrested, tortured, victimised, jailed, and have been subjected to practices that contravene international law. Some of them were able to flee the country and settled in Europe, Canada, and the United States. This study used a narrative synthesis of qualitative design. By analysing the critical life stories of those who have fled, this article provides a narrative, in-depth exploration of their experiences in the Turkish turmoil. A purposive sample of 15 Turkish intellectuals was utilised, and the data were collected through semi-structured interviews from December 2018 to June 2019. Two main themes emerged: torture and right to a fair trial. The results of this study showed the depths of the persecution, torture, and humiliation that the men, women, and children who were detained and jailed endured. The results also showed the most violated human rights were torture, some of which resulted in deaths in custody and the absence of a fair trial.
Keywords: Human rights violations; tortures; right to a fair trial; state of emergency; narrative study; Turkey; Government & Law